INTERACTIVE LEARNING INNOVATION: IMPROVING UNDERSTANDING OF THE CONCEPTS OF MOTION AND FORCE IN PROSPECTIVE TEACHER STUDENTS - Ibrahim, Ibrahim; Maimun, Maimun; Bahtiar, Bahtiar; Suranti, Ni Made Yeni (MO.RI Publishing, 2024)
This research aims to measure the effectiveness of interactive learning media in increasing understanding of the concepts of movement and force in prospective elementary school teacher students. The research subjects were 26 students who took a test based on the Quizizz application, consisting of 12 multiple choice questions and short answers. The research results showed a gradual increase in answer accuracy, especially on the final questions, with the highest accuracy of 70% on the 12th question. Meanwhile, the initial questions showed low accuracy, which indicated the need to strengthen basic concepts. Analysis of processing time shows that students who spend more time tend to get better results. The frequency distribution of correct answers shows that the majority of students are in the middle ability category, while only a few achieve high performance. These findings imply the need to use varied learning strategies, such as interactive simulations, virtual experiments, or problem-based discussions, to increase in-depth understanding of concepts. Thus, interactive learning media can be an effective solution in supporting the learning process in the field of science education.